2015
DOI: 10.1080/15299732.2014.991861
|View full text |Cite
|
Sign up to set email alerts
|

Childhood trauma and complex posttraumatic stress disorder symptoms in older adults: A study of direct effects and social-interpersonal factors as potential mediators

Abstract: Childhood traumatic events may lead to long-lasting psychological effects and contribute to the development of complex posttraumatic sequelae. These might be captured by the diagnostic concept of complex posttraumatic stress disorder (CPTSD) as an alternative to classic posttraumatic stress disorder (PTSD). CPTSD comprises a further set of symptoms in addition to those of PTSD, namely, changes in affect, self, and interpersonal relationships. Previous empirical research on CPTSD has focused on middle-aged adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 40 publications
(45 reference statements)
3
28
1
1
Order By: Relevance
“…By contrast, repeated traumas often take the form of chronic physical, sexual, or psychological trauma, as well as prolonged torture, and are associated with dissociation, a psychological escape when a physical escape is not possible (Choi, Lee, & Lee, ; Cloitre et al, ; Hagan, Gentry, Ippen, & Lieberman, ; Herman, ; Palic, Carlsson, Armour, & Elklit, ; for a review, see Dalenberg et al, ; Lyssenko et al, ; Putnam, ; Schauer & Elbert, ; Vermetten, Dorahy, & Spiegel, ). These traumas are frequently experienced during childhood or during prolonged torture, where the survivor is less equipped to defend against the perpetrator and, in turn, may feel helpless throughout their experience (Krammer, Kleim, Simmen‐Janevska, & Maercker, ; Kratzer et al, ; for a review, see Foa & Hearst‐Ikeda, ; van der Kolk, ). Under these conditions, active defenses can be perceived as futile and, hence, discarded for a passive response.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, repeated traumas often take the form of chronic physical, sexual, or psychological trauma, as well as prolonged torture, and are associated with dissociation, a psychological escape when a physical escape is not possible (Choi, Lee, & Lee, ; Cloitre et al, ; Hagan, Gentry, Ippen, & Lieberman, ; Herman, ; Palic, Carlsson, Armour, & Elklit, ; for a review, see Dalenberg et al, ; Lyssenko et al, ; Putnam, ; Schauer & Elbert, ; Vermetten, Dorahy, & Spiegel, ). These traumas are frequently experienced during childhood or during prolonged torture, where the survivor is less equipped to defend against the perpetrator and, in turn, may feel helpless throughout their experience (Krammer, Kleim, Simmen‐Janevska, & Maercker, ; Kratzer et al, ; for a review, see Foa & Hearst‐Ikeda, ; van der Kolk, ). Under these conditions, active defenses can be perceived as futile and, hence, discarded for a passive response.…”
Section: Introductionmentioning
confidence: 99%
“…Trauma, adversity, and stress exposure can have lasting negative effects on psychological health and well-being. In particular, early-life adversity (such as trauma, maltreatment, or neglect) has been shown to lead to long-term health-related problems and the development of mental health disorders ( 1 , 2 ). For instance, a large-scale study by the World Health Organization (WHO) examined the prevalence of mental health disorders across 21 countries.…”
Section: Introductionmentioning
confidence: 99%
“…This research examined psychopathological and resilient outcomes in an adult sample of former indentured child laborers in Switzerland (i.e., the so-called Verdingkinder) . Many former Verdingkinder experienced high levels of exposure to trauma and maltreatment in childhood, including physical, emotional, and sexual abuse, as well as physical and emotional neglect ( 1 , 12 ). Findings showed that some former Verdingkinder had developed mental health disorders in later life: 23% major depressive disorder, 26.3% posttraumatic stress disorder, and 7.8% generalized anxiety disorder ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, we can speculate that perhaps the length of time between childhood and older adulthood negatively affects memory, or perhaps that long-term exposure to homelessness and the risks associated with it affects memory and/or older adults may be less likely to speak about childhood trauma than younger adults. It may be more likely, however, as Krammer et al (2016) argued, that childhood trauma in older adults manifests as classic PTSD and its symptoms rather than as other mental health issues. It is important to note that whereas older adults reported, on average, two fewer childhood traumatic experiences than younger adults, the average ACE score for the general population is 1.4 (Troy, 2014), the average for our sample of older adults was 3.4, or two and half times higher.…”
Section: Discussionmentioning
confidence: 99%